The Republic of Birds: the construction of the city and the citizenship according to Plato and Aristophanes - Alexandre da Silva Costa (O Que Nos Faz Pensar, 2018)
Carrying out a comparative analysis between its primary sources, this article is about the construction of the “ideal city” in the works of Plato and Aristophanes and their correlate conceptions of citizenship, proposing, specifically, that the foundation of the city, as exposed in the Republic, is in close dialogue and in intense confrontation with the creation of the city comically conceived by Aristophanes in The Birds.